Dwelling in different localities: Identity performances of a white transnational professional elite in the City of London and the Central Business District of Singapore. Issue 3 (3rd May 2016) - Meier, Lars
ABSTRACT: Besides being mobile, migrant professionals dwell at specific localities. It is in this article that identity performances of one social group with equal identity dimensions, white, male German financial manager, are compared in two different local contexts of their dwelling: in the City of London and in the Central Business District of Singapore. This article demonstrates that by comparing similar social groups in different localities, the effects of locality become clearly visible. As the managers are temporal migrants, their dwelling practices are to arrange themselves with locality for the time of their delegation. Everyday practices and the specific symbolic labelling of localities are expressions and producers of identity. The mobile managers encounter the two localities with unique images rooted in the colonial period; as a centre and an outpost, respectively. As these images have an impact on their identity performances today, this article demonstrates that the mangers perform whiteness and being transnational elite with different emphasis regarding locality.